2010
DOI: 10.4161/adna.1.1.12199
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nucleic acid probes with charged photocleavable mass markers

Abstract: Halogen-labelled peptide organic acid (HPOA) monomers have been synthesised and incorporated into sequence-specific peptide nucleic acid (PNA) probes. Three different types of probe have been prepared; the unmodified PNA probe, the PNA probe with a mass marker, and the PNA probe with photocleavable mass marker. All three types of probe have been used in model studies to develop a mass spectrometry-based hybridisation assay for detection of point mutations in DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…An alternative to using uorescent tags is the use of cleavable small molecule mass tags, which can be employed for the indirect analysis of large biomolecules with detection by mass spectrometry. Mass tags have been used for oligonucleotide analysis where a small molecule label was conjugated to an oligonucleotide probe via a synthetic photocleavable linker which was cleaved during the matrix-assisted desorption/ionisation (MALDI) process [7][8][9][10] or a synthetic linker cleaved during the electrospray ionisation (ESI) process. 11 Previous work has shown that the ribose-phosphate backbone of RNA can be used as a built-in enzyme cleavable linker, which upon cleavage of custom designed oligonucleotides with a specic ribonuclease can produce mono-di-or trinucleotide digestion products.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to using uorescent tags is the use of cleavable small molecule mass tags, which can be employed for the indirect analysis of large biomolecules with detection by mass spectrometry. Mass tags have been used for oligonucleotide analysis where a small molecule label was conjugated to an oligonucleotide probe via a synthetic photocleavable linker which was cleaved during the matrix-assisted desorption/ionisation (MALDI) process [7][8][9][10] or a synthetic linker cleaved during the electrospray ionisation (ESI) process. 11 Previous work has shown that the ribose-phosphate backbone of RNA can be used as a built-in enzyme cleavable linker, which upon cleavage of custom designed oligonucleotides with a specic ribonuclease can produce mono-di-or trinucleotide digestion products.…”
Section: Introductionmentioning
confidence: 99%
“…The design of the photocleavable building block was based on o -nitrobenzyl esters. Further applications followed, including photolabile solid supports, photocleavable mass tags, , photolabile circular antisense oligonucleotides, and negatively charged peptide nucleic acids (caged ncPNAs) for gene regulation. Alternative photocleavable linkages based on the phenacyl ester group were previously used to connect active oligonucleotides to solid supports or for immobilization of RNA aptamers on microbeads …”
mentioning
confidence: 99%